University Students with PCOS Demonstrate Limited Nutrition Knowledge. Issue 2 (4th March 2021) - Douglas, Crystal Clark; Jones, Rachel; Green, Rachel; Brown, Kristina; Yount, Greschen; Williams, Robert
ABSTRACT: Background : Dietary modification is critical for the management of polycystic ovary syndrome (PCOS), yet few women with PCOS report receiving nutrition education. Nutrition knowledge may translate to dietary behaviors and diet quality, but nutrition knowledge among women with PCOS is unknown. Purpose : Using a descriptive design, we assessed nutrition knowledge, diet quality, and eating disorder risk among university students with PCOS. Methods : Following clinical and biochemical analysis, 12 university students with PCOS were admitted to the study. Participants completed validated questionnaires (Nutrition Knowledge Questionnaire, Eating Disorder Examination-Questionnaire 6.0 (EDE-Q 6.0), 3-day food records, and body composition testing. Results : Participants were obese (75%), insulin resistant (58%), and consumed an unbalanced diet (41% carbohydrate, 43% fat). Bread or fruit were avoided by 27.3%. Nutrition knowledge was poor (48% correct) and inversely related to fruit intake (r(9) = −.689, p < .05). Nearly half (41.6%) were at increased risk for eating disorders (EDE-Q score ≥ 4). Discussion : University students with PCOS demonstrate poor nutrition knowledge, consume an unbalanced and limited diet, and exhibit an increased risk for eating disorders. Translation to Health Education Practice : University-health service programs targeting nutrition education and behavior modification are needed to improve the management and mitigation of PCOS-related symptoms in students. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars